طبيعة عقوبة التشغيل الاجتماعي كأحد العقوبات البديلة في التشريعات المقارنة - الأطرش, عصام حسني; الهاجري, دلهم ناصر (University of Eloued جامعة الوادي, 2019)
تناولت هذه الدراسة طبيعة عقوبة التشغيل الاجتماعي كأحد العقوبات البديلة في التشريعات المقارنة، حيث تطرق الباحثان إلى ماهية عقوبة التشغيل الاجتماعي من حيث مفهومها وخصائصها وأصل الفكرة، بالإضافة إلى فلسفة تلك العقوبة وتأثيراتها، كما تطرق الباحثان إلى احكام عقوبة التشغيل الاجتماعي في التشريعات المقارنة والإجراءات التي تتبع عنج تنفيذ عقوبة التشغيل الاجتماعي، وقد توصل الباحثان إلى أهمية تطبيق وتفعيل عقوبة التشغيل الاجتماعي لما تحققه من فائدة بالنسبة للمحكوم عليه والمجتمع . This study deals with the nature of the of social employment penalty as one of the alternative penalties in the comparative legislations, The researchers focus on the the concept of social employment penalty from many aspects like its concept, characteristics, the origin of the idea, in the addition to the philosophy of the punishment and its effects, The researchers also discussed the provisions of the social employment penalty in the comparative legislations and the procedures that are followed in the implementation of social employment penalty. The researchers concluded to the importance of applying and activating for social employment penalty for the benefit it achieves for the convicted person and society.
مجلد3، عدد3
Keywords: عقوبة التشغيل الاجتماعي، العقوبات البديلة، التشريعات المقارنة; social employment penalty, alternative penalties, comparative legislations.